PENGARUH FAKTOR EKSPOSI TERHADAP KUALITAS CITRA RADIOGRAFI PADA PEMERIKSAAN THORAX - Raditya Faradina Pratiwi; Elitha Sundari Pulungan; Dewi Andini (JRI (Jurnal Radiografer Indonesia), 2023)
ABSTRACT Background: The exposure factor is one of the factors that influence and determine the quality and quantity of X-ray radiation required in making radiographic images. Every radiographic examination requires precision in the use of exposure factors in both conventional radiographic modalities and in the use of CR. Selection of the right exposure factor using both conventional radiography and Computed Radiography (CR) can produce radiographs with optimal results. Methods: This type of research is a library research or literature review by reviewing as many as 50 journals related to image quality on radiograph of thorax during the last 10 years. Then the researchers screened the journals related to the the effect of exposure factors on image quality radiograph of thorax in as many as 4 journals . Results: Image quality analysis is carried out based on image visualization (observation) parameters which include contrast and image sharpness. The exposure factors of 60 kV and 25 mAs in the image shows good gradations, namely the difference from bright white to perfect grayish black and the difference between the phantom object and the area around the object. When using a 60 kV tube voltage, you can see abnormalities in the ribs. Using exposure factors of 75 kV and 3.2 mAs and 65 kV and 8 mAs the resulting images have the highest contrast. Conclusions: Based on the review results, there are several exposure factors that can be used in thorax examination, including 55 kV and 8 mAs due to factor regulation. This exposure is the optimization of the PA thorax examination, the use of the 60 kV and 25 mAs exposure factors, radiographic images can be read and have met good image quality on the object and 60 kV produces maximum contrast, this is in accordance with the theory of using tube voltage to see abnormalities that occurs in the ribs. The highest contrast on the chest X-ray image was obtained using the exposure factors of 75 kV and 3.2 mAs and 65 kV and 8 mAs.